An In Vitro Comparative Study of Intracanal Fluid Motion and Wall Shear Stress Induced by Ultrasonic and Polymer Rotary Finishing Files in a Simulated Root Canal Model. (11th March 2012) - Koch, Jon; Borg, John; Mattson, Abby; Olsen, Kris; Bahcall, James
Abstract : Objective . This in vitro study compared the flow pattern and shear stress of an irrigant induced by ultrasonic and polymer rotary finishing file activation in an acrylic root canal model. Flow visualization analysis was performed using an acrylic canal filled with a mixture of distilled water and rheoscopic fluid. The ultrasonic and polymer rotary finishing file were separately tested in the canal and activated in a static position and in a cyclical axial motion (up and down). Particle movement in the fluid was captured using a high-speed digital camera and DaVis 7.1 software. The fluid shear stress analysis was performed using hot film anemometry. A hot-wire was placed in an acrylic root canal and the canal was filled with distilled water. The ultrasonic and polymer rotary finishing files were separately tested in a static position and in a cyclical axial motion. Positive needle irrigation was also tested separately for fluid shear stress. The induced wall shear stress was measured using LabVIEW 8.0 software.